2012
DOI: 10.1037/a0028590
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perspectives on providing support to children after trauma: A qualitative study.

Abstract: A considerable number of children are exposed to extreme stressors such as the sudden loss of a loved one, serious traffic accidents, violence, and disaster. In order to facilitate school psychologists' assistance of teachers working with traumatized children, this study aimed to explore elementary school teachers' perspectives. Using a qualitative design, the study explored the perspectives of a purposively varied sample of 21 elementary school teachers (ages 22-55 years; with 0.5-30 years of teaching experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
130
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(140 citation statements)
references
References 31 publications
8
130
1
1
Order By: Relevance
“…It is not expected that school staff 'treat' or assume a formal ongoing counselling role when engaging with a young person who has self-harmed. Indeed, it is clear that boundaries are required between the roles of teachers and other school staff and those of mental health professionals (Alisic, 2012). However, once self-harm is detected they do have a role in sign posting further help and intervention available to the student (Doyle, Keogh & Morrissey, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is not expected that school staff 'treat' or assume a formal ongoing counselling role when engaging with a young person who has self-harmed. Indeed, it is clear that boundaries are required between the roles of teachers and other school staff and those of mental health professionals (Alisic, 2012). However, once self-harm is detected they do have a role in sign posting further help and intervention available to the student (Doyle, Keogh & Morrissey, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The 37 schools that had participated in two earlier studies on child trauma (Alisic, 2011;Alisic, Van der Schoot, Van Ginkel, & Kleber, 2008) were excluded from the list. From the remaining pool, a contact list of 2,000 schools was drawn up, using the random sampling function of SPSS 17 (SPSS Inc., 2009).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…If knowledgeable, they can also provide coping assistance including emotional processing, distraction, and the reinstitution of familiar roles and routines (Prinstein, La Greca, Vernberg, & Silverman, 1996 Although a number of studies have shown the positive effects of teacher-mediated interventions related to mass-trauma such as war and disaster (e.g., Wolmer, Hamiel, Barchas, Slone, & Laor, 2011;, little is known about teachers' support of children in daily school life who have been exposed to a variety of traumatic events. An unpublished qualitative study (Alisic, 2011) suggested that elementary school teachers are uncertain about their role and about what to do to assist children effectively after traumatic exposure. Participants indicated a lack of guidance on how to balance the needs of the children who had been exposed against the needs of the other children in the classroom, as well as their own needs, and wanted better knowledge and skills about helping children after trauma.…”
mentioning
confidence: 98%
“…This highlights the role of schools, recreational organisations and the broader community in supporting positive outcomes for children and young people and the importance of directing post-disaster services accordingly [13,17,18,[44][45][46].…”
Section: Discussionmentioning
confidence: 94%